Human Cytomegalovirus Immediate Early Protein 2 Protein Causes Cognitive Disorder by Damaging Synaptic Plasticity in Human Cytomegalovirus-UL122-Tg Mice - Wang, Zhifei; Yu, Wenwen; Liu, Lili; Niu, Junyun; Zhang, Xianjuan; Nan, Fulong; Xu, Lili; Jiang, Bin; Ke, Dingxin; Zhu, Wenhua; Tian, Zibin; Wang, Yashuo; et al. (Frontiers in Aging Neuroscience, 2021)
Human cytomegalovirus (HCMV) infection is very common in the human population all around the world. Although the majority of HCMV infections are asymptomatic, they can cause neurologic deficits. Previous studies have shown that immediate early protein 2 (IE2, also known as UL122) of HCMV is related with the cognitive disorder mechanism. Due to species isolation, a HCMV-infected animal model could not be established which meant a study into the long-term effects of IE2 on neural development could not be carried out. By establishing HCMV-UL122-Tg mice (UL122 mice), we explored the cognitive behavior and complexity of neuron changes in this transgenic UL122 mice that could consistently express IE2 protein at different ages (confirmed in both 6- and 12-month-old UL122 mice). In the Morris water maze, cognitive impairment was more pronounced in 12-month-old UL122 mice than in 6-month-old ones. At the same time, a decrease of the density of dendritic spines and branches in the hippocampal neurons of 12-month-old mice was observed. Moreover, long-term potentiation was showed to be impaired in 12-month-old UL122 mice. The expressions of several synaptic plasticity-regulated molecules were reduced in 12-month-old UL122 mice, including scaffold proteins postsynaptic density protein 95 (PSD95) and microtubule-associated protein 2 (MAP2). Binding the expression of IE2 was increased in 12-month-old mice compared with 6-month-old mice, and results of statistical analysis suggested that the cognitive damage was not caused by natural animal aging, which might exclude the effect of natural aging on cognitive impairment. All these results suggested that IE2 acted as a pathogenic regulator in damaging synaptic plasticity by downregulating the expression of plasticity-related proteins (PRPs), and this damage increased with aging.